"Diversity in the Workplace": Indonesian Muslim Migrant Workers' Experiences in Japan - Widarahesty, Yusy (Global Strategis, 2024)
A rapidly shrinking and aging population has pushed the Japanese government to relax certain border regulations to let in more foreign workers. JICA predicts that by 2040, Japan will need to double its foreign workforce to more than 6 million. This is also in line with the Japanese government’s policy plan which opens up opportunities for foreign workers to enter from various countries through technical intern trainee visas, specified skilled workers, professional workers, etc. As a result, under the Abe administration, the Japanese government launched the Diversity and Empowerment in the Workplace campaign to welcome international workers as one of the social integration policies to achieve harmony. Thus, this paper aims to analyze how the synergy of diversity in workplace policy toward Muslim migrant workers in Japan progresses by using ethnography and participant observation as a methodological approach. Qualitative data was collected between 2018 and 2023 through participant observations and semi structured interviews. By looking at the stories conveyed, it seems that the ‘diversity in workplace policies’ cannot yet be adequately implemented for Muslim workers, especially those with semi-skilled visa categories such as trainees and SSW. Furthermore, social integration efforts through workplace diversity policies are hampered because some Japanese companies continue to have a bad working culture that promotes productivity by imposing long working hours. This has become a problem for Japanese workers and has prompted criticism and efforts to change. Keywords: “Diversity in the workplace”, Indonesian Migrant Workers, Muslim, Japan Populasi yang menyusut dan menua dengan cepat telah mendorong pemerintah Jepang untuk melonggarkan peraturan perbatasannya agar dapat menerima lebih banyak pekerja asing. JICA memperkirakan Jepang perlu meningkatkan jumlah tenaga kerja asing sebanyak empat kali lipat menjadi lebih dari enam juta pada tahun 2040. Hal ini juga sejalan dengan rencana kebijakan pemerintah Jepang yang membuka peluang masuknya tenaga kerja asing dari berbagai negara melalui berbagai jenis visa seperti pemagang kerja, pekerja berketerampilan khusus, pekerja profesional, dll. Oleh karena itu, untuk menyambut masuknya pekerja asing, pemerintah Jepang pada masa pemerintahan Abe telah mencanangkan slogan keberagaman dan pemberdayaan di lingkungan kerja sebagai upaya strategi integrasi sosial. Berdasarkan hal tersebut, penelitian ini bertujuan untuk menganalisis bagaimana sinergitas kebijakan keberagaman di tempat kerja Jepang terhadap pekerja migran Muslim di Jepang dengan menggunakan etnografi dan observasi partisipan sebagai pendekatan metodologis. Data kualitatif dikumpulkan antara tahun 2018 sampai 2023 melalui observasi partisipan dan wawancara semi terstruktur. Dengan melihat kisah-kisah yang disampaikan, tampaknya ‘kebijakan keberagaman di tempat kerja’ belum dapat diterapkan secara memadai bagi pekerja Muslim, terutama mereka yang memiliki kategori visa semi-terampil seperti pekerja magang dan pekerja Spesial Skill Workers/SSW. Lebih jauh, upaya integrasi sosial melalui kebijakan keberagaman di tempat kerja terhambat karena buruknya budaya kerja di beberapa perusahaan Jepang yang mempromosikan produktivitas dengan memberlakukan jam kerja yang panjang. Hal tersebut menjadi masalah bagi pekerja Jepang dan telah memicu kritik serta upaya untuk berubah. Kata-kata Kunci: “Diversity in the workplace”, Pekerja Migran Indonesia, Muslim Indonesia, Jepang